2009
DOI: 10.1101/gad.1861409
|View full text |Cite
|
Sign up to set email alerts
|

miR-19 is a key oncogenic component of mir-17-92

Abstract: Recent studies have revealed the importance of multiple microRNAs (miRNAs) in promoting tumorigenesis, among which mir-17-92/Oncomir-1 exhibits potent oncogenic activity. Genomic amplification and elevated expression of mir-17-92 occur in several human B-cell lymphomas, and enforced mir-17-92 expression in mice cooperates with c-myc to promote the formation of B-cell lymphomas. Unlike classic protein-coding oncogenes, mir-17-92 has an unconventional gene structure, where one primary transcript yields six indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
527
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(568 citation statements)
references
References 54 publications
25
527
3
6
Order By: Relevance
“…5A). Luciferase reporter gene assay confirmed that the miR‐17~92 cluster directly targets the 3′UTRs of the Pten and p21 genes, as shown in Figure 5B and C in accordance with previous reports 17, 27. Our immunoblotting results revealed that the loss of miR‐17~92 caused slight changes in the levels of cyclin D1, Pten and p21 levels in the male mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…5A). Luciferase reporter gene assay confirmed that the miR‐17~92 cluster directly targets the 3′UTRs of the Pten and p21 genes, as shown in Figure 5B and C in accordance with previous reports 17, 27. Our immunoblotting results revealed that the loss of miR‐17~92 caused slight changes in the levels of cyclin D1, Pten and p21 levels in the male mice (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Elevated miR17-92 levels have been associated with invasion and metastasis of colorectal cancer cells (32), and poorer survival (33). miR19a and miR19b in particular are key oncogenic determinants (29,30), and both were significantly elevated with the HRM diet compared with the entry diet. miR21 has similarly been classed as oncogenic, and can also induce tumorigenesis, invasion, and metastasis (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…HRM intake significantly increased rectal mucosa levels of miR17-92 cluster miRNAs and miR21, which are both elevated in colorectal cancer (16,17). The miR17-92 cluster has been designated oncomir-1 (31), and can promote proliferation and angiogenesis, inhibit differentiation, and sustain cell survival (29,30). Elevated miR17-92 levels have been associated with invasion and metastasis of colorectal cancer cells (32), and poorer survival (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐19 promotes tumourigenesis by regulating target genes and related signalling pathways. In human B‐cell lymphomas, miR‐19 promotes tumour cell survival by inhibiting PTEN directly and activating AKT/mTOR pathway 22. Expression of miR‐19 is elevated in SHH medulloblastoma, a subgroup of medulloblastoma characeterized as constitutive activation of the Sonic Hedgehog pathway, anti‐miR‐19 treatment restrains proliferation of tumour cells and prolongs survival of tumour‐bearing mice23 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%